Motion Event Similarity Judgments in One or Two Languages: An Exploration of Monolingual Speakers of English and Chinese vs. L2 Learners of English - Ji, Yinglin (Frontiers in Psychology, 2017)
Languages differ systematically in how to encode a motion event. English characteristically expresses manner in verb root and path in verb particle; in Chinese, varied aspects of motion, such as manner, path and cause, can be simultaneously encoded in a verb compound. This study investigates whether typological differences, as such, influence how first and second language learners conceptualise motion events, as suggested by behavioural evidences. Specifically, the performance of Chinese learners of English, at three proficiencies, was compared to that of two groups of monolingual speakers in a triads matching task. The first set of analyses regarding categorisation preferences indicates that participants across groups preferred the path-matched (rather than manner-matched) screens. However, the second set of analyses regarding reaction time suggests, firstly, that English monolingual speakers reacted significantly more quickly in selecting the manner-matched scenes compared with monolingual speakers of Chinese, who tended to use an approximately equal amount of time in making manner- and path-matched decisions, a finding that can arguably be mapped onto the typological difference between the two languages. Secondly, the pattern of response latency in low-level L2 learners looked more like that of monolingual speakers of Chinese. Only at intermediate and advanced levels of acquisition did the behavioural pattern of L2 learners become target-like, thus suggesting language-specific constraints from the L1 at an early stage of acquisition. Overall, our results suggest that motion event cognition may be linked to, among other things, the linguistic structure of motion description in particular languages.